Margret & H.A. Rey's Curious George and the firefighters - Rey, Margret; Rey, H. A. (Hans Augusto), 1898-1977.; Hines, Anna Grossnickle (Boston : Houghton Mifflin Harcourt, 2010)
While on a field trip to a fire station with Mrs. Gray's class, Curious George goes off on his own and is soon at the scene of a fire, where he finds a way to be helpful.
2.8
K-3
Text in Spanish and English.
Translation of: Margret & H.A. Rey's Curious George and the firefighters.
K-3
AD490L
Keywords: Curious George (Fictitious character) -- Juvenile fiction; Monkeys -- Juvenile fiction; Fire fighters -- Juvenile fiction; Fire departments -- Juvenile fiction; School field trips -- Juvenile fiction; Curious George (Fictitious character) -- Fiction; Spanish language materials -- Bilingual; Monkeys -- Fiction; Fire fighters -- Fiction; Fire departments -- Fiction; School field trips -- Fiction; Curious George (Fictional character) -- Fiction; Bilingual books -- English-Spanish.; Monkeys -- Fiction; Fire fighters -- Fiction; Fire departments -- Fiction; Field trips -- Fiction; Picture books for children